"Being a bully isn't very cool…": Rap & Sing Music Therapy for enhanced emotional self-regulation in an adolescent school setting – a randomized controlled trial. (July 2018) - Uhlig, Sylka; Jansen, Erik; Scherder, Erik
Music as an effective self-regulative tool for emotions and behavioural adaptation for adolescents might enhance emotion-related skills when applied as a therapeutic school intervention. This study investigated Rap & Sing Music Therapy in a school-based programme, to support self-regulative abilities for well-being. One-hundred-and-ninety adolescents in grade 8 of a public school in the Netherlands were randomly assigned to an experimental group involving Rap & Sing Music Therapy or a control group. Both interventions were applied to six classes once a week during four months. Measurements at baseline and again after four months provided outcome data of adolescents' psychological well-being, self-description, self-esteem and emotion regulation. Significant differences between groups on the SDQ teacher test indicated a stabilized Rap & Sing Music Therapy group, as opposed to increased problems in the control group ( p = .001; ηp 2 = .132). Total problem scores of all tests indicated significant improvements in the Rap & Sing Music Therapy group. The RCT results imply overall benefits of Rap & Sing Music Therapy in a school setting. There were improved effects on all measures – as they are in line with school interventions of motivational engagement in behavioural, emotional and social themes – a promising result.